The contribution of character education management to enhancing students' discipline - Muhammad Yunus Nasution; Aulia Ukhtin; Fatmawarni Fatmawarni (Lembaga Riset Mutiara Akbar, 2026)
This study examines the contribution of character education management to enhancing students’ discipline in educational institutions. A qualitative descriptive approach was employed using library research supported by relevant books, journal articles, and educational policy documents. Data were analyzed through data reduction, data display, and conclusion drawing to identify key themes related to character education management. The findings indicate that effective character education management is reflected in systematic planning, implementation, supervision, and evaluation integrated into both curricular and extracurricular activities. These management practices contribute to strengthening students’ disciplinary attitudes by fostering responsibility, self-control, and positive behavioral habits. However, the implementation has not yet achieved optimal outcomes due to various internal and external challenges, including limited stakeholder involvement and inconsistencies in program execution. The study emphasizes that sustainable collaboration among school leaders, teachers, parents, and the community is essential for developing a strong culture of discipline. Strengthening management practices and continuously evaluating character education programs are expected to improve the effectiveness of discipline development and support the achievement of broader educational goals.